(untitled) (Scientific journal of the Fergana State University, 2026)
In the context of the rapid development of modern information technologies and the widespread dissemination of mass communication tools, information and media literacy are becoming crucial factors in ensuring national security, particularly among the youth. Threats within the global information space, the spread of misinformation, propaganda, and manipulation can negatively affect young people’s consciousness. This article analyzes the role of media and information literacy in the national security system, its main goals and objectives, particularly its importance in protecting information sovereignty, countering information and psychological attacks, strengthening social cohesion, and enhancing conscious decision-making.